High throughput sequencing technologies complemented by growers’ perceptions highlight the impact of tomato virome in diversified vegetable farms and a lack of awareness of emerging virus threats - Temple, Coline; Blouin, Arnaud G.; Tindale, Sophie; Steyer, Stephan; Marechal, Kevin; Massart, Sebastien (Frontiers in Sustainable Food Systems, 2023)
The number of small-scale diversified vegetable growers in industrialized countries has risen sharply over the last 10 years. The risks associated with plant viruses in these systems have been barely studied in Europe, yet dramatic virus emergence events, such as tomato brown fruit rugose virus (ToBRFV), sometimes occur. We developed a methodology that aimed to understand better the implications related to viruses for tomato production in Belgian’s vegetable farms by comparing growers’ perception and the presence of plant-viral-like symptoms (visual inspection) with non-targeting detection of nearly all viruses present in the plants by high throughput sequencing technologies (HTS). Virus presence and impact were interpreted considering the farm’s typology and cultural practices, and the grower’s professional profiles. Overall, the data indicated that most growers have limited understanding of tomato viruses and are not concerned about them. Field observations were correlated to this perception as the prevalence of symptomatic plants was usually lower than 1%. However, important and potentially emergent viruses, mainly transmitted by insects, were detected in several farms. Notably, the presence of these viruses tended to be associated with the number of plant species grown per site (diversity) but not with a higher awareness of the growers regarding plant viral diseases, or a higher number of symptomatic plants. In addition, both HTS and perception analysis underlined the rising incidence and importance of an emergent virus: Physostegia chlorotic mottle virus. This study also revealed a notable lack of knowledge among producers regarding the highly contagious quarantine virus ToBRFV. Overall, the original methodology developed here, involving the integration of two separate fields of study (social science with phytopathology using HTS technologies), could be applied to other crops in other systems to identify emergent risks associated with plant viruses, and can highlight the communication needed with growers to mitigate epidemics. This exploratory investigation provides relevant insights, which, ideally, would be further tested on wider samples to allow finer statistical treatment to be performed.